2019
DOI: 10.1021/acs.iecr.9b00485
|View full text |Cite
|
Sign up to set email alerts
|

The Polarity of Ionic Liquids: Relationship between Relative Permittivity and Spectroscopic Parameters of Probe

Abstract: Polarity is one of the most important properties of ionic liquids (ILs) and an essential requirement when choosing an IL for a specific industrial application. Up to now, several empirical solvent polarity scales, such as Hildebrand solubility parameter, relative permittivity, the electronic transition energy of the longest-wavelength Vis absorption band of betaine dye no. 30 (E T (30) value) and the hyperfine coupling constant (A N ) etc. have been applied to ILs to provide quantitative evaluation of the pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 135 publications
1
16
0
Order By: Relevance
“…When applying PCM, the solvent parameters of ILs are necessary. The dielectric constant and refractive index of studied ILs were estimated 15.0 and 1.43, respectively, based on the published works [34][35][36] . All the above calculations were performed by employing Gaussian09 package 37 .…”
Section: Articlementioning
confidence: 99%
“…When applying PCM, the solvent parameters of ILs are necessary. The dielectric constant and refractive index of studied ILs were estimated 15.0 and 1.43, respectively, based on the published works [34][35][36] . All the above calculations were performed by employing Gaussian09 package 37 .…”
Section: Articlementioning
confidence: 99%
“…Therefore, it is important to know the polarity of an IL before it can be utilized for specific purpose. In addition, ILs have a wide range of miscibility [34,35]. -Electrolytic properties of ILs: ILs are better electrolytes, however for the charges to move freely, the ionic compounds must be converted into molten form prior to their application.…”
Section: Characteristic Properties Of Ionic Liquidsmentioning
confidence: 99%
“…Therefore, it is important to know the polarity of an IL before it can be utilized for specific purpose. In addition, ILs have a wide range of miscibility 34, 35. Electrolytic properties of ILs: ILs are better electrolytes, however for the charges to move freely, the ionic compounds must be converted into molten form prior to their application. Designer solvent: The name designer solvent is used for ILs because a large number of ILs can by prepared by selecting appropriate cations and anions, modifying ILs through attachment of functional groups into the cations and/or anions and by mixing two or more simple ILs 36. Chemical stability of ILs: The chemical stability of ILs in various types of reagents are under investigation. Among various classes of ILs, the ILs containing imidazolium cations have gained much importance for various applications due to their easy preparation and thermal and chemical stability to reductive and oxidative conditions 37–39.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 1 – 3 are synthesized for the first time in this study, whereas the preparation and thermal properties of 4 have been previously reported . In addition, we evaluate the solvent polarity parameters ( E T N and the Kamlet–Taft parameters) of the synthesized ILs, noting that the solvent polarity parameters of a number of onium-based ILs have been previously measured using solvatochromic dyes, including their temperature dependence. Finally, the solvato- and thermochromic properties of the IVCR bands of the dinuclear ILs are examined.…”
Section: Introductionmentioning
confidence: 99%